2021
DOI: 10.1371/journal.pone.0253606
|View full text |Cite
|
Sign up to set email alerts
|

Association of lung function with functional limitation in older adults: A cross-sectional study

Abstract: Introduction Impaired lung function is independently associated with higher rates of disability, however, few studies have examined the association between lung function and functional limitation. This study aimed to assess this association and dose-response relationship in older adults. Methods Data from the National Health and Nutrition Examination Survey (2007–2012) was used as a cross-sectional study. Lung function was determined by Forced expiratory volume in 1 second (FEV1) and forced vital capacity (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In addition, the 6-min walk distance was notably lower in patients with comorbid sarcopenia than in patients without comorbid sarcopenia, and the mMRC score and BODE index was increased in patients with comorbid sarcopenia than in patients without comorbid sarcopenia. Considering that COPD is both an airway and systemic inflammatory disease, a high concentration of inflammatory factors could affect muscle atrophy and decreased muscle function ( 90 , 91 ). A study involving 164 older adults suggested that interleukin-6 levels were negatively associated with skeletal muscle mass index and grip strength, whereas tumor necrosis factor-α and C-reactive protein levels were negatively associated with muscle mass and strength ( 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the 6-min walk distance was notably lower in patients with comorbid sarcopenia than in patients without comorbid sarcopenia, and the mMRC score and BODE index was increased in patients with comorbid sarcopenia than in patients without comorbid sarcopenia. Considering that COPD is both an airway and systemic inflammatory disease, a high concentration of inflammatory factors could affect muscle atrophy and decreased muscle function ( 90 , 91 ). A study involving 164 older adults suggested that interleukin-6 levels were negatively associated with skeletal muscle mass index and grip strength, whereas tumor necrosis factor-α and C-reactive protein levels were negatively associated with muscle mass and strength ( 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that forced vital capacity is also an independent mediator in the relationship between MVPA and FOF. It is highly rational that there is a significant correlation between strenuous MVPA and forced vital capacity, which was found associated with functional performance in older adults ( 42 , 74 , 75 ). However, so far, no study has directly investigated the association between forced vital capacity and FOF in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study showed that ~40% of patients with chronic lung diseases were prone to suffer some degree of disability and 68% lost at least one relevant function of daily living ( 22 ). Gao and colleagues also reported that those with poor lung function, as assessed by the FVC < 0.76 criterion, would be at nearly twice the risk of developing functional limitation ( 23 ).…”
Section: Discussionmentioning
confidence: 99%